Potential roles of IL-38, among other inflammation-related biomarkers, in predicting post-percutaneous coronary intervention cardiovascular events - Kou, Lu; Yang, Ning; Dong, Bo; Qin, Qin (Frontiers in Cardiovascular Medicine, 2024)
Percutaneous coronary intervention (PCI), as a relatively rapid and effective minimally invasive treatment for coronary heart disease (CHD), can effectively relieve coronary artery stenosis and restore myocardial perfusion. However, major adverse cardiovascular events (MACE) occurrence is a significant challenge for post PCI care. To better understand risk/benefit indicators and provide post PCI MACE prediction, 408 CHD patients undergone PCI treatment from 2018 to 2021 in Tianjin Chest hospital were retrospectively studied on their clinical characteristics in relation with the MACE occurrence during a 12-month followup. In the study 194 patients had MACE and 214 patients remain MACE-free. Using uni and multivariate regression analysis, we have shown that smoking history, elevated serum Creactive protein levels (hs-CRP), and high haemoglobin levels A1c (HbA1c) are all independent risk factors for MACE after PCI. Furthermore, we have discovered that the serum level of IL-38 , one of the latest members identified in the IL-1 cytokine family, is another predictive factor and is reversely related to the occurrence of MACE. The serum level of IL-38 alone is capable of predicting non-MACE occurrence in subcategorised patients with abnormal levels of hs-CRP and / or HbA1c.